Hubungan Antara Kemampuan Menyimak Dongeng terhadap Kemampuan literasi Membaca Anak SD yang Ikut Komunitas Rumah Baca - Muthiah, Siti; Lestari, Mas Roro Wahyu Diah (Syntax Literate, 2025)
The ability to listen to fairy tales has an important role in improving children's reading literacy skills, especially for elementary school children who are involved in the reading house community. This study aims to determine the relationship between the ability to listen to fairy tales and the ability to read literacy in children. The method used is a quantitative approach, with data collection through questionnaires or questionnaires The findings of the study revealed that children who can listen to fairy tales well generally have better reading comprehension, a wider vocabulary, and the ability to identify the main ideas in the text more effectively. In addition, the involvement of children in the reading home community provides a greater boost in listening and reading activities, which in turn increases their interest and motivation towards literacy. Therefore, listening to fairy tales can be used as an effective strategy to improve children's reading literacy skills, especially in a supportive community environment such as a reading house.